Teaching children to write and read in Waldorf schools - Bell, Amanda (Frontiers in Education, 2024)
A well-established principle of Waldorf Education is that children's development is compromised if we bring intellectual teaching too early. Waldorf teachers congratulate themselves that they wait until the seventh year to begin formal schooling, but according to the principles out of which Waldorf Education arose, teaching children to read and write at seven is not ideal; they are still not ready.Convention and state expectations made it necessary in 1919 to introduce literacy at an age close to what was considered normal, so a compromise was needed. Steiner suggested that, because physical development reaches a certain completion at seven, it is less harmful if we wait until then, but this was still a compromise: we cannot unleash any kind of teaching scheme on seven-year-olds without doing any harm. According to modern teaching principles, starting earlier means getting ahead; everything should be taught explicitly and nothing left to develop of its own accord. 1 Proponents of synthetic phonics refer to research showing that it produces the best results 2 , which is why it has been adopted so widely in mainstream education. However, the validity of this claim depends on what we mean by 'better results' and 'literacy'. This paper explores these ideas.1 Ken Robinson, Out of Our Minds: The Power of Being Creative (2017) Capstone Press, Mankato Minnesota 2 A longitudinal study reported by Johnston and Watson (2005) found that a group taught by synthetic phonics had better spelling, word reading and comprehension than a group taught by analytic phonics.